Traumatic upper limb weakness in a man with type 1 neurofibromatosis - Ng, Esther Shu-Ting; Ong, Cheng Kang; Wilder-Smith, Einar (Journal of neurology, neurosurgery, and psychiatry, 2011)
A 37-year-old right-handed man presented with left arm weakness 4 months after a shoulder trauma, which was caused by somebody landing on him while swimming. There was initial left upper limb numbness and neck pain radiating to the left back with subsequent weakness of shoulder movement. He had type 1 neurofibromatosis (NF-1) with skin manifestations but no known neurological complication. - - On examination, power of shoulder abduction, flexion and extension and elbow flexion on the left was 2 (Medical Research Council grade), shoulder elevation was 4+ and there was moderate scapular winging. Power of all other muscle groups was 5. Left biceps and triceps reflexes were decreased. Sensation was normal as was the rest of the neurological examination. - - Nerve …
Gesehen am 22.09.2022